Enhanced Ex Vivo Expansion of Human Hematopoietic Progenitors on Native and Spin Coated Acellular Matrices Prepared from Bone Marrow Stromal Cells - Samiksha Wasnik; Suma Kantipudi; Mark A. Kirkland; Gopal Pande (Stem Cells International)
The extracellular microenvironment in bone marrow (BM) is known to regulate the growth and differentiation of hematopoietic stem and progenitor cells (HSPC). We have developed cell-free matrices from a BM stromal cell line (HS-5), which can be used as substrates either in native form or as tissue engineered coatings, for the enhanced ex vivo expansion of umbilical cord blood (UCB) derived HSPC. The physicochemical properties (surface roughness, thickness, and uniformity) of native and spin coated acellular matrices (ACM) were studied using scanning and atomic force microscopy (SEM and AFM). Lineage-specific expansion of HSPC, grown on these substrates, was evaluated by immunophenotypic (flow cytometry) and functional (colony forming) assays. Our results show that the most efficient expansion of lineage-specific HSPC occurred on spin coated ACM. Our method provides an improved protocol for ex vivo HSPC expansion and it offers a system to study the in vivo roles of specific molecules in the hematopoietic niche that influence HSPC expansion.